Fulminant Invasive Aspergillosis in a Previously Healthy Woman After Cesarean Section and a Review of the Literature - Luca Pipitò; Gennaro Baldino; Giovanni Bartoloni; Maurizio Sanguinetti; Elvira Ventura Spagnolo; Antonio Cascio (Infectious Disease Reports)
Background: Invasive aspergillosis is an extremely rare condition in healthy and immunocompetent individuals, and very few cases have been reported in previously healthy, pregnant, or postpartum women. Method: We describe a case of invasive aspergillosis in a puerperal patient and present literature review results. Case: We present a case of fulminant invasive pulmonary aspergillosis with cerebral, cardiac, and gastric involvement in a young woman, occurring a few days after an elective cesarean section. The patient succumbed after intensive care unit admission, and the diagnosis was made postmortem through autopsy. Conclusion: A total of 20 cases of invasive aspergillosis have been previously reported in pregnant or postpartum women, with high mortality. The risk of opportunistic fungal infections during pregnancy and postpartum should not be underestimated.